The role of control-ownership wedge in moderating the influence of board diversity and audit committee on audit quality - Mustafa, Aree Saeed (2018)
The objective of this study is to examine the effect of board diversity and audit committee on audit quality with respect to the influence of a wedge (divergence between control rights and cash flow rights) in Turkey. Turkey has made essential amendments in the field of external audit in order to enhance the quality of financial report and integrate its own capital market with that of EU. An analysis of the influence of these changes should be of interest to examine its influence on clients demand for high quality audit. This study used the data of 146 firms listed on the Borsa Istanbul (BIST) over the period from 2011 to 2015. Using logistic regression and Feasible Generalized Least Square (FGLS), the findings explained that clients’ incentives and abilities to demand high audit quality increased because of board demographics, cognitive and structural diversity and the audit committee proxies (by audit committee size, audit committee independence and audit committee meeting). However, the wedge weakened the influence of board diversity and the audit committee to demand high audit quality, which will be an unfavourable outcome for the minority shareholders. Thus, this study proposes that regulators, particularly the Capital Market Board of Turkey (CMBT), should increase law enforcement to enhance good corporate governance in Turkey to accommodate the unique features of wedge firms and provide a protected environment for investors particularly, the minority shareholders.